The Development of a Marketing Tourism Model Toward Intention to Visit and Decision to Visit in Leading Tourism Object - Mutia Tri Satya; Yuyus Yudistria; Muhammad Asdar; Andi Abdul Razak Munir (Journal of Management Practices, Humanities and Social Sciences, 2019)
The purpose of this study is to develop a model of marketing tourism at the leading tourism object in Bandung and Soppeng, Indonesia. This model will be linked to its influence with the intention to visit and the decision to visit. At the present time, Bandung and Soppeng strives to become one of the tourist destinations both in Indonesia and in the world. Improvement of facilities and infrastructure facilities is carried out by the government to provide comfort for tourists who are increasing in number to visit. Data is collected through questionnaires, interviews, observation and secondary data. Simple random sampling is used for distributing questionnaires to respondents. Respondents in this study were 100 tourists from city of Bandung, as well as 100 respondents who were tourists in Soppeng Regency. Data processing techniques use Structural Equation Modeling (SEM) to conduct analysis among several dependent and independent variables directly. The results of this study analyze the dimensions of each variable marketing tourism (economy, social, culture, information technology, environment), intention to visit (interest, searching information, preferences) and decision to visit (attitude, memory, perception, need). The dimensions of each variable showed the magnitude of the effect. Bandung a value of 6.62% for the construct of decision to visit, value is also found in intention to visit which is influenced by tourism marketing of 5.74%. Soppeng values for the decision to visit construct 7.33%, and value is also found in intention to visit which is influenced by tourism marketing of 7.09%. which means that the influence between significant constructs. The model developed in current study is expected to be applicable in terms of tourism development.